Discovery of Inhibitors of Insulin-Regulated Aminopeptidase as Cognitive Enhancers. (4th December 2012) - Andersson, Hanna; Hallberg, Mathias
Abstract : The hexapeptide angiotensin IV (Ang IV) is a metabolite of angiotensin II (Ang II) and plays a central role in the brain. It was reported more than two decades ago that intracerebroventricular injection of Ang IV improved memory and learning in the rat. Several hypotheses have been put forward to explain the positive effects of Ang IV and related analogues on cognition. It has been proposed that the insulin-regulated aminopeptidase (IRAP) is the main target of Ang IV. This paper discusses progress in the discovery of inhibitors of IRAP as potential enhancers of cognitive functions. Very potent inhibitors of the protease have been synthesised, but pharmacokinetic issues (including problems associated with crossing the blood-brain barrier) remain to be solved. The paper also briefly presents an overview of the status in the discovery of inhibitors of ACE and renin, and of AT1R antagonists and AT2R agonists, in order to enable other discovery processes within the RAS system to be compared. The paper focuses on the relationship between binding affinities/inhibition capacity and the structures of the ligands that interact with the target proteins.